2011
DOI: 10.1371/journal.pone.0028871
|View full text |Cite
|
Sign up to set email alerts
|

Restored Circulating Invariant NKT Cells Are Associated with Viral Control in Patients with Chronic Hepatitis B

Abstract: Invariant NKT (iNKT) cells are involved in the pathogenesis of various infectious diseases. However, their role in hepatitis B virus (HBV) infection is not fully understood, especially in human species. In this study, 35 chronic hepatitis B (CHB) patients, 25 inactive carriers (IC) and 36 healthy controls (HC) were enrolled and the proportions of circulating iNKT cells in fresh isolated peripheral blood mononuclear cells (PBMC) were detected by flow cytometry. A longitudinal analysis was also conducted in 19 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Because HBsAg has been demonstrated to directly suppress both innate immunity and adaptive immunity to HBV infection thus allowing HBV to evade the immune system and establish a persistent infection, we sought to investigate whether Peg‐IFN add‐on strategy might be associated with changes in two different subsets of unconventional T cells. Alongside T and NK cells, unconventional T cells including iNKT cells and TCR γδ T cells are endowed with bridging properties between innate and adaptive immune responses within both peripheral blood and the liver …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because HBsAg has been demonstrated to directly suppress both innate immunity and adaptive immunity to HBV infection thus allowing HBV to evade the immune system and establish a persistent infection, we sought to investigate whether Peg‐IFN add‐on strategy might be associated with changes in two different subsets of unconventional T cells. Alongside T and NK cells, unconventional T cells including iNKT cells and TCR γδ T cells are endowed with bridging properties between innate and adaptive immune responses within both peripheral blood and the liver …”
Section: Discussionmentioning
confidence: 99%
“…A few contradictory results have been published on the frequency and function of peripheral iNKT cells in HBV infection, partially explained by the different methods used to identify iNKT cells. In agreement with the previous findings, we observed low frequencies of circulating iNKT cells with high interindividual variability (range = 0.01%‐0.4% in CD3+ T cells), although our cohort of HBV chronically infected subjects on suppressive NA therapy displayed decreased frequencies of iNKT than those observed in healthy controls, independently from the presence of cirrhosis or ALT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Its antiviral activities toward HBV infection have been demonstrated in previous studies (Kakimi et al, 2000;Zeissig et al, 2012). In our previous studies, we found that the peripheral NKT expression level in the active phase of the immune response was significantly higher than that during the immune tolerance phase (Huang, 2007;Jiang et al, 2011). Therefore, further observation was performed to determine whether Peg-INF therapy could regulate the body's immune cells and activate the in vivo expression of natural killer (NK)/NKT cells, thus improving antiviral activities.…”
Section: Introductionmentioning
confidence: 70%
“…α‐GalCer‐activated invariant NK T (iNKT) cells are able to inhibit HBV replication in vivo, suggesting that NKT cells are part of an early sensing system and may further prime HBV‐specific adaptive immune response. However, the number of circulating iNKT cells in CHB patients is lower compared with healthy donors and inactive healthy HBV carriers, while it increases to normal levels when HBV infection was controlled by antiviral therapy with telbivudine …”
Section: Hbv Persistence Induces Systemic Innate Immune Tolerancementioning
confidence: 98%